Measuring the nursing work environment: translation and psychometric evaluation of the Essentials of Magnetism. (26th November 2013) - de, B.J.M.; Kaljouw, M.J.; Kramer, M.; Schmalenberg, C.; van, T.
<x xml:space="preserve">Abstract</x> Aim Translate the Essentials of Magnetism II© (EOMII; Dutch Nurses' Association, Utrecht, The Netherlands) and assess its psychometric properties in a culture different from its origin. Background The EOMII, developed in the USA, measures the extent to which organizations/units provide healthy, productive and satisfying work environments. As many healthcare organizations are facing difficulties in attracting and retaining staff nurses, the EOMII provides the opportunity to assess the health and effectiveness of work environments. Methods A three‐phased (respectively N = 13, N = 74 and N = 2542) combined descriptive and correlational design was undertaken for translation and evaluation validity and psychometric qualities of the EOMII for Dutch hospitals (December 2009–January 2010). We performed forward‐backward translation, face and content validation via cross‐sectional survey research, and semi‐structured interviews on relevance, clarity, and recognizability of instruments' items. Psychometric testing included principal component analysis using varimax rotation, item‐total statistics, and reliability in terms of internal consistency (Cronbach's α) for the total scale and its subscales. Results Face validity was confirmed. Items were recognizable, relevant and clear. Confirmatory factor analysis indicated that five of eight subscales formed clear factors. Three original subscales contained two factors. Item‐total correlations ranged from 0.43 to 0.83. One item correlated weakly (0.24) with its subscale. Cronbach's α for the entire scale was 0.92 and ranged from 0.58 to 0.92 for eight subscales. Conclusions Dutch‐translated EOMII (D‐EOMII) demonstrated acceptable reliability and validity for assessing hospital staff nurses' work environment. Implications for Nursing and Health Policy The D‐EOMII can be useful and effective in identifying areas in which change is needed for a hospital to pursue an excellent work environment that attracts and retains well‐qualified nurses.